Rebranding Opak Gambir Cahaya Kita Sebagai Upaya Meningkatkan Brand Awareness - Mochammad Rayyan Thalib; Ayundha Evanthi (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Assistance in community service programs with an entrepreneurial and creative economy scheme by the East Java National "Veteran" Development University in the Merdeka Learning KKN-T program - Merdeka Campus which aims to solve the problems faced by UMKM Opak Gambir Cahaya Kita which is engaged in selling light snacks, namely many competitors in the market and less related to brand awareness. The method used is to conduct a survey combined with interviews in addition to the Forum Group Discussion (FGD) combined with brainstorming and distributing questionnaires. The benefits of research are knowing the importance of brand awareness which affects brand awareness to consumers and the level of consumer purchasing power in the market, in addition to the successful rebranding of logos, stickers and packaging which will later be used by MSME assistance partners Opak Gambir Cahaya Kita after the mentoring program is carried out